Microwave radiometry of vegetation canopies - Chukhlantsev, Alexander A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Research into microwave radiation from the Earth$1 (Bs surface in the presence of vegetation canopies, as well as the development of algorithms for retrieval of soil and vegetation parameters from microwave radiometric measurements, have been actively conducted for the last 30 years by scientific groups worldwide. The capability of the microwave radiometric method to determine soil moisture and vegetation biometric indices was revealed 25 years ago by the author and his colleagues. Soil moisture and vegetation covers play a key role in the hydrological cycle and in water and energy transfer on the border of land surface and atmosphere through evaporation and transpiration. Accomplishment of large international projects shows that microwave radiometry of soil and vegetation has become an instrument of practical application and operational use. A systematic account of questions concerning the microwave radiometry of the Earth$1 (Bs surface in the presence of vegetation canopies is the main objective of the book.s
Basics of microwave radiometry -- Physical and electrical properties of soils and vegetation -- Microwave emission from bare soils -- Theory of microwave propagation through vegetation media -- Experimental studies of microwave propagation in vegetation canopies -- Modeling of microwave emission from vegetation canopies -- Experimental research on microwave emission from vegetation canopies -- Vegetation effect in microwave remote sensing -- Microwave radiometry of vegetation canopies in context of global change research.
Keywords: Environment; Remote sensing; Optics; Electrodynamics; Microwaves; Optical engineering; Climate change; Environment; Climate Change; Optics and Electrodynamics; Microwaves, RF and Optical Engineering; Remote Sensing/Photogrammetry.; Electronic books